Effects of perioperative steroid use on surgical stress and prognosis in patients undergoing hepatectomy: a systematic review and meta-analysis of randomized controlled trials - Furui Zhong; Hua Yang; Xuefeng Peng; Kerui Zeng (Frontiers in Pharmacology)
The objective of this study was to evaluate the clinical effects of perioperative steroid hormone usage in hepatectomy patients through a comprehensive systematic review and meta-analysis. Prospective randomized controlled trials (RCTs) investigating the perioperative use of steroid hormones in hepatectomy patients were systematically searched using various databases, including PubMed, Medline, Embase, the Cochrane Library, the Chinese Biomedical Literature Database, Wanfang Data, and the CNKI database. Two researchers independently screened and extracted data from selected studies. Data analysis was performed using RevMan 5.3 software. The results revealed significantly lower levels of total bilirubin (standard mean difference [SMD] = −0.7; 95% CI: −1.23 to −0.18; and p = 0.009), interleukin-6 (SMD = −1.02; 95% CI: −1.27 to −0.77; and p < 0.001), and C-reactive protein (SMD = −0 .65; 95% CI: −1 .18 to −0.11; and p = 0.02) on postoperative day 1 (POD 1), as well as a reduced incidence of postoperative complications in the steroid group compared to the placebo group. No significant differences were observed between the two groups regarding alanine aminotransferase (ALT) levels, aspartic aminotransferase (AST) levels, or specific complications such as intra-abdominal infection (p = 0.72), wound infection (p = 0.1), pleural effusion (p = 0.43), bile leakage (p = 0.66), and liver failure (p = 0.16). The meta-analysis results indicate that perioperative steroid usage can effectively alleviate liver function impairment and inflammation response following hepatectomy while improving patient prognosis.